Socio-philosophical research and evaluation methodology of the internationalisation of higher education - Smaliakou, Dzmitry A. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The internationalisation of higher education is an important direction of modern interdisciplinary research, where one of the most difficult problems is the research and evaluation methodology. Philosophy consists of the necessary methodological tools that may assist for accurate solution of this problem, both in the terms of efficiency, and within the framework of a broader discussion regarding modern methods of research in humanities. The proposed context targeting method is the further development of postmodern methodological tools, such as narratives and discourses analysis. Within the framework of the proposed research and evaluation method, the university or national higher education system activity is considered as context, where should be determined for observation a set of sensitive elements, that assists to identify ongoing changes or the absence of such. As a result of such an observation, the researcher acquires objective data that allows to judge the nature of the internationalisation of higher education, as well as to evaluate its efficiency.
Keywords: internationalisation of higher education; context targeting; research and evaluation methodology; science methodology